(3cfGT UgGQHNJ aj GdWHs - (3CHhRjO UgGQHNJ Hf eGSQLSs; (3UgGQHNJ Hf eGSQLS, CHh jRjOs
(3ChdgG (B:s
(3GdMeO ddg GdPi de jRd HOjFkG HZQ HOA SCdJfi jGHf YjSi , Rjfc Gddg HGMceI hUGfc ef GdTHgI YfO fXQc aj GdcJGH GdPi Cdag LhQLjS GdLfO jSGHhQi aj UfGYI GdWH Cf CTQM dc ZhGeV JOHjQGJg s
(3BNQgG (B:s
(3hLeY GdYUHI CjVkG UYHI dbQHgG ef GdbdH decGf ChGdeQI GdUaQGA GdaGYdI dgG agPG eG ENJefG cJGHfG s
(3hgh TQM cfT LhQLjSs
(3YdjgG hbajI SfI (B1145 (3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B209 s
Keywords: (3GdWHs